2021
DOI: 10.3390/fi13080193
|View full text |Cite
|
Sign up to set email alerts
|

Education 4.0: Teaching the Basics of KNN, LDA and Simple Perceptron Algorithms for Binary Classification Problems

Abstract: One of the main focuses of Education 4.0 is to provide students with knowledge on disruptive technologies, such as Machine Learning (ML), as well as the skills to implement this knowledge to solve real-life problems. Therefore, both students and professors require teaching and learning tools that facilitate the introduction to such topics. Consequently, this study looks forward to contributing to the development of those tools by introducing the basic theory behind three machine learning classifying algorithms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 50 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…There are some similar studies to ours but using a different dataset from the Wisconsin Breast Cancer database [22][23][24]. Using a larger dataset with more features, these studies have shown the feasibility of machine learning based models in predicting breast cancer risks in the healthcare domains.…”
Section: Background and Related Workmentioning
confidence: 79%
“…There are some similar studies to ours but using a different dataset from the Wisconsin Breast Cancer database [22][23][24]. Using a larger dataset with more features, these studies have shown the feasibility of machine learning based models in predicting breast cancer risks in the healthcare domains.…”
Section: Background and Related Workmentioning
confidence: 79%
“…In education, the convergence of these technologies is often referred to as “Education 4.0,” not only where predictive models of student achievement may be constructed but also where teaching and learning approaches may be optimized. Lopez-Bernal et al (2021) caution, however, technologies need to complement human sensemaking and problem-solving:…”
Section: Resultsmentioning
confidence: 99%
“…This study discusses the application of different algorithms to solve three different binary classification problems using three different datasets. Comparisons are made in specific case studies and their performance; it is proved that the optimized performance is the best [ 24 ].…”
Section: Resultsmentioning
confidence: 99%